Effectiveness and safety of lubiprostone after switching from stimulant laxatives in elderly patients with chronic constipation - Masaki Maruyama; Suguru Miida; Toshihiro Sato; Takazumi Kimura; Azuma Watanabe; Hideo Watanabe; Masafumi Nishizawa; Kyohei Horikawa; Takahiro Kajiwara; Yusuke Karasawa; Yuko Hasebe; Kazutaka Nozawa; et al. (JGH Open, 2023)
Abstract Background and Aim Stimulant laxatives may cause electrolyte abnormalities, dehydration, and abdominal pain; their long‐term use can lead to tolerance and subsequent refractory constipation. We investigated the effectiveness, safety, and quality of life after switching from stimulant laxatives to lubiprostone in elderly patients with chronic constipation (CC). Methods This multicenter, interventional, open‐label, single‐arm, before‐and‐after comparison study enrolled 99 Japanese patients aged 65–90 years with CC who took stimulant laxatives for ≥2 weeks prior to switching to lubiprostone monotherapy. Results The mean ± SD spontaneous defecations at Week 1 of 7.8 ± 6.2 times/week was not significantly different from that at baseline (8.3 ± 4.7). Spontaneous defecations were significantly reduced at Weeks 2 (−1.5 ± 4.0, P < 0.001) and 4 (−1.5 ± 3.7, P < 0.001). The Bristol Stool Form Scale score did not change from baseline (4.7 ± 0.9) at Weeks 1 (4.5 ± 1.3) or 4 (4.3 ± 1.3), but it did at Week 2 (4.3 ± 1.5, P < 0.05). The Patient Assessment of Constipation Quality of Life questionnaire score increased (0.36 ± 0.07, P < 0.001) after 28 days. Nausea was the only symptom that worsened from baseline and was the most frequently reported adverse drug reaction (15.2%). Conclusion Switching to lubiprostone monotherapy for CC was not associated with significant concerns in short‐term spontaneous defecation frequency and safety, but it might affect the efficacy and patient quality of life over 2 weeks. Careful treatment strategies facilitating gradual switching to lubiprostone monotherapy may be needed in patients using stimulant laxatives.